First report of leaf spot disease on oil palm caused by Pestalotiopsis theae in Thailand - Nakarin Suwannarach (2018)
A leaf spot on oil palm, caused by Pestalotiopsis theae, was found in a plantation of Elaeis guineensis for the first time in the world in Chiang Mai Province, Thailand. The fungus was isolated from lesions on leaves, and its pathogenicity was confirmed. Pathogenicity tests showed that P. theae could infect E. guineensis, which developed the same symptoms after inoculation as those observed naturally in the field. The fungus was identified based on morphological characteristics and confirmed using comparisons of DNA sequences of internal transcribed spacer (ITS)1, ITS2 and 5.8S rDNA. This report is the first on oil palm leaf spot disease caused by P. theae. © 2013 The Phytopathological Society of Japan and Springer Japan.